Pengembangan Media English Vocabulary Card di UPTD SD Negeri 017107 Kisaran Naga - Radode Kristianto Simarmata; Nancy Angelia Purba; Jon Roi Tua Purba (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The background for the development of English Vocabulary Card media is to look at the state of learning media in general. In elementary schools the use of media that speaks vocabulary is still very minimal. Even though learning media is needed to make it easier for teachers to transfer knowledge and make it easier for students to understand English vocabulary. This study uses research and development methods or Research and Development (R&D). After developing students' English learning with English Vocabulary Card Media Development at UPTD SD Negeri 017107 Kisaran Naga, learning proved to be more effective. Therefore, the researchers developed English Vocabulary Card media for fourth grade English subjects. This study aims to develop learning media in the form of English vocabulary cards and find out how the appropriateness of the media is so that it produces media that is valid, effective and responsive. The data collection technique in this study was to use a research and development questionnaire to produce English vocabulary card media that was feasible to use based on assessments from media experts, material experts, English subject teachers and students' responses.